Customer Loyalty In E-Commerce: An Exploration Of Its Influencing Factors - Ikramuddin, Ikramuddin; Mariyudi, Mariyudi; Matriadi, Faisal; Roni, Muhammad; Ahyar, Juni (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2024)
The purpose of this study is to ascertain the impact of electronic word-of-mouth, trust, and customer satisfaction on customer loyalty among Lhokseumawe City Lazada users. The primary data utilized in this study was collected by giving questionnaires to 140 consumers in Lhokseumawe City who had purchased products using the Lazada application. With the aid of SPSS software version 26, multiple linear regression is the data analysis technique employed. The findings indicated that partial satisfaction, trust, and electronic word-of-mouth had a favorable and significant impact on customer loyalty for Lazada users in Lhokseumawe City.